2017
DOI: 10.22296/2317-1529.2017v19n2p326
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial de equipamentos de mamografia no Brasil

Abstract: R e s u m o : Este trabalho avalia a rede de oferta de mamógrafos no Brasil a partir da disponibilidade regional do equipamento e da distância entre demanda potencial e oferta de equipamentos no âmbito municipal. Os resultados demonstram que a quantidade total de mamógrafos no Brasil seria suficiente para o atendimento da população, dada a previsão de necessidade estipulada pela nota técnica do Instituto Nacional do Câncer (INCA). Todavia, quando se limita o alcance da oferta a uma distância de 60 km, é possív… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
1
9
0
8
Order By: Relevance
“…Factors such as cultural differences, socioeconomic differences, geographical location, and limited information on the part of the population can also impede access to health care services, thus increasing disparity (41,45) . The low rates of mammography coverage found in the present study underscore the need to research the geographic distribution of the mammography equipment available via the SUS and the influence that it can have on access to the test (16,42) .…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as cultural differences, socioeconomic differences, geographical location, and limited information on the part of the population can also impede access to health care services, thus increasing disparity (41,45) . The low rates of mammography coverage found in the present study underscore the need to research the geographic distribution of the mammography equipment available via the SUS and the influence that it can have on access to the test (16,42) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the need of mammography calculated by the ministerial parameters totalled in about 12.5 million exams, with an excess of offering 11.1%. 19 In this regard, this study shows that Pernambuco State does not comply with this national trend of over offering of mammograms performed by SUS.…”
Section: Discussionmentioning
confidence: 66%
“…24,25 This leads us to affirm that even if the equipment is available, this does not guarantee access, but without the availability of it there is no access any way. 19 The capacity used on the mammography equipment did not reach 50% in all the health regions in the state, ranging from 4% to 42%. A national study carried out in 2016 6 showed the relation between low mammography coverage for the population and the aspects related to socioeconomic conditions in the Regions and States can generate this difference, as well as the poor distribution of the equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to reflect on the distribution of health services and to consider the capacity that users have to appropriate care in order to provide conditions of equal access to people with equal needs 18 .…”
Section: Discussionmentioning
confidence: 99%